Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1039/c8sc01186a
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of low-density lipoprotein receptor degradation with a cyclic peptide that disrupts the homodimerization of IDOL E3 ubiquitin ligase

Abstract: A cyclic peptide IDOL homodimerization inhibitor identified from a genetically encoded SICLOPPS library is active in vitro and in cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Although effective IDOL-targeted therapies have yet to be developed, several recent studies have demonstrated that natural compounds including docosahexanoic acid and xantholhumol modulate hepatic LDLR abundance via suppression of IDOL expression 16 , 17 . In addition, a recent study identified a cyclic peptide that disrupts IDOL homodimerization as an IDOL inhibitor and showed that it increased LDLR levels in HepG2 cells 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Although effective IDOL-targeted therapies have yet to be developed, several recent studies have demonstrated that natural compounds including docosahexanoic acid and xantholhumol modulate hepatic LDLR abundance via suppression of IDOL expression 16 , 17 . In addition, a recent study identified a cyclic peptide that disrupts IDOL homodimerization as an IDOL inhibitor and showed that it increased LDLR levels in HepG2 cells 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other ubiquitinated proteins, the ubiquitinated LDLR is easy to degrade. Unlike other ubiquitinated proteins, which degraded in proteasome where IDOL also catalyzes its own degradation, LDLR is usually degraded in lysosomes 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…2019). The system can also be utilized to discover inhibitors of protein dimerization like the cyclic peptide inhibitors found to prevent the homodimerization of IDOL E3 ubiquitin ligase with a K D of 4.6 µM (Leitch et al, 2018) and BCL6 with a K D of 142 µM (Osher et al, 2018). In addition, even correctors of protein misfolding can be identified using SICLOPPS-based screening (Matis et al, 2017).…”
Section: Protein Splicing Methodsmentioning
confidence: 99%